2017
DOI: 10.1007/s00586-017-5425-8
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism in junctional failure of thoraco-lumbar fusions. Part I: Biomechanical analysis of mechanisms responsible of vertebral overstress and description of the cervical inclination angle (CIA)

Abstract: The T1-T5 segment inclination is correlated with the C7 slope, and because the latter defines the cervical curve as previously shown, the T1-T5 segment can be considered as the base from which the cervical spine originates. Its role is, thus, similar to the pelvis and its sacral slope, which is the base from which the lumbar spine originates. The CIA along with the ODHA, which describes the adequacy of the global balance in young and elderly asymptomatic populations, are two important parameters that could hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
2
23
0
3
Order By: Relevance
“…The analysis of sagittal balance is critically important to optimize the management of lumbar degenerative diseases, especially when spinal instrumentation is intended [ 2 , 40 ]. It was reported that the cervical inclination angle (CIA) and along with the OD-HA, which describes the adequacy of the global balance in young and elderly asymptomatic populations, are two important parameters that could affect junctional breakdowns in thoraco-lumbar fusion surgeries [ 41 ]. The preoperative sagittal malalignment or imbalance showed a significant relationship with incidence of proximal junctional kyphosis (PJK).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of sagittal balance is critically important to optimize the management of lumbar degenerative diseases, especially when spinal instrumentation is intended [ 2 , 40 ]. It was reported that the cervical inclination angle (CIA) and along with the OD-HA, which describes the adequacy of the global balance in young and elderly asymptomatic populations, are two important parameters that could affect junctional breakdowns in thoraco-lumbar fusion surgeries [ 41 ]. The preoperative sagittal malalignment or imbalance showed a significant relationship with incidence of proximal junctional kyphosis (PJK).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the preoperative C7-SVA demonstrated a significant relationship with incidence of PJK [ 42 ]. The weight of the head in different inclination angles can cause different torque on spinal column, which may lead to different degree of injuries to the spine [ 41 ]. In our study, there were close relations between the position of the head and the spinal-pelvic alignment and back muscles indicating the underlying compensated mechanisms [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dies führt zu einer Ventralverlagerung des Schwerpunktes mit erhöhten Biegemomenten im Bereich des thorakolumbalen Überganges. Bei multiplen Degenerationen der Bandscheiben kann die entstehende Kyphose vergleichbare biomechanische Eigenschaften auf den oberen Nachbarwirbel erzeugen wie bei einer Kyphose durch eine Kompressionsfraktur [17]. Mit der Anzahl der in kyphotischer Fehlstellung verheilten Frakturen verschiebt sich die vertikale sagittale Achse weiter nach vorne und erhöht somit die Belastung auf die Wirbelsäule mit der Gefahr weiterer Anschlussfrakturen, sog.…”
Section: Biomechanische Besonderheitenunclassified
“…Entstehen durch diese Kräfte weitere Frakturen und werden diese operativ versorgt, ohne eine operative Korrektur der sagittalen Balance, verbleibt weiterhin die hohe kyphosebedingte Belastung, welche sich nun auf die darüberliegenden Wirbelkörper überträgt. Biomechanisch führt erst eine zusätzliche Korrektur der Kyphose in ein balanciertes Profil zu weniger Biegemomenten [17].…”
Section: Biomechanische Besonderheitenunclassified
“…Changes in forces and moments acting on the spine after spinal instrumentation surgery may be directly involved in structural failure due to proximal segment overload. Excessive compressive loads may cause vertebral body fractures [18,19], excessive tension-disruption of ligaments [18] and shear overloadfacet joint injuries and pedicle fractures [20].…”
Section: Introductionmentioning
confidence: 99%